Adenosine deaminase-1 enhances germinal center formation and functional antibody responses to HIV-1 Envelope DNA and protein vaccines. Issue 22 (8th May 2020) - Gary, Ebony; O'Connor, Margaret; Chakhtoura, Marita; Tardif, Virginie; Kumova, Ogan K.; Malherbe, Delphine C.; Sutton, William F.; Haigwood, Nancy L.; Kutzler, Michele A.; Haddad, Elias K.
Highlights: We show ADA enhances human DC differentiation and promote a TFH polarizing cytokines. We have determined that ADA selectively enhances GC-TFH frequency in vivo. ADA improves the quality of anti-HIV antibodies, generating neutralizing antibodies. Abstract: Adenosine deaminase-1 (ADA-1) plays both enzymatic and non-enzymatic roles in regulating immune cell function. Mutations in the ADA1 gene account for 15% of heritable severe-combined immunodeficiencies. We determined previously that ADA1 expression defines and is instrumental for the germinal center follicular helper T cell (TFH ) phenotype using in vitro human assays. Herein, we tested whether ADA-1 can be used as an adjuvant to improve vaccine efficacy in vivo . In vitro, ADA-1 induced myeloid dendritic cell (mDC) maturation as measured by increased frequencies of CD40-, CD83-, CD86-, and HLA-DR-positive mDCs. ADA-1 treatment also promoted the secretion of the TFH -polarizing cytokine IL-6 from mDCs. In the context of an HIV-1 envelope (env) DNA vaccine, co-immunization with plasmid-encoded ADA-1 (pADA) enhanced humoral immunity. Animals co-immunized with env DNA and pADA had significantly increased frequencies of TFH cells in their draining lymph nodes and increased HIV-binding IgG in serum. Next, mice were co-immunized with subtype C env gp160 DNA and pADA along with simultaneous immunization with matched gp140 trimeric protein. Mice that received env gp160 DNA, pADA, and gp140 glycoprotein had significantly more heterologous HIV-specific binding IgG in their serum. Furthermore, only these mice had detectable neutralizing antibody responses. These studies support the use of ADA-1 as a vaccine adjuvant to qualitatively enhance germinal center responses and represent a novel application of an existing therapeutic agent that can be quickly translated for clinical use.